O capital digital e os desafios na sociedade em rede: um estudo multidimensional da divisão digital - Dias, Elaine Cristina Ferreira (2023)
This thesis aimed to explore the digital divide within a country, focusing on the asymmetry of digital capital and its relationship with online opportunities and benefits. The study used both quantitative and qualitative approaches, involving Portuguese citizens, immigrants, and non-immigrants. The starting point of our analysis focused on a conceptual research model that was replicated in nine research hypotheses, articulated with the dimensions of digital capital and digital divide, previously described, and which were validated throughout this thesis with the results of the empirical study. The empirical data analysis revealed that education level and age are key factors influencing the use of online services and individuals' digital capital. The qualitative interviews shed light on reasons for not using online services, trusting false information on social networks, and intentions to continue using digital services postpandemic. This research contributes to the understanding of digital inequalities and the attribution of digital skills in the third level of the digital divide, an area that has been relatively unexplored in empirical studies within Information Science.